2016
DOI: 10.1371/journal.pone.0157217
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Uptake of Visual Inspection with Acetic Acid (VIA) for Cervical Cancer Screening in Western Kenya

Abstract: PurposeCervical cancer screening has been successful in reducing the rates of cervical cancer in developed countries, but this disease remains the leading cause of cancer deaths among women in sub-Saharan Africa. We sought to understand factors associated with limited uptake of screening services in our cervical cancer-screening program in Western Kenya.Participants and MethodsUsing items from a previously validated cancer awareness questionnaire repurposed for use in cervical cancer and culturally adapted for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
4
22
0
2
Order By: Relevance
“…Among both HIV‐positive and HIV‐negative women, a high proportion of women were not aware of the test. About two‐third of the cohorts were not aware of the cervical cancer screening test, which is lower than in countries such as Kenya and Uganda . A large proportion of HIV‐positive women reported economical reasons for not undergoing cervical cancer screening, which is commonly reported in developing countries .…”
Section: Discussionmentioning
confidence: 97%
“…Among both HIV‐positive and HIV‐negative women, a high proportion of women were not aware of the test. About two‐third of the cohorts were not aware of the cervical cancer screening test, which is lower than in countries such as Kenya and Uganda . A large proportion of HIV‐positive women reported economical reasons for not undergoing cervical cancer screening, which is commonly reported in developing countries .…”
Section: Discussionmentioning
confidence: 97%
“…The sensitivity and specificity of screening tests and the efficacy of treatment options replicated reported parameters from recent Kenyan studies among WHIV in care (table 1). Also, rates of individuals refusing CC screening services and LTFU reflect those observed in programmatic evaluations within HIV care facilities in Kenya 9 10 20–23. Individuals for whom treatment was effective and who recovered were assumed to remain cervical disease free for 24 months and, as above, go back to susceptible thereafter and be at risk of new HPV infections accounting for their age and ART status.…”
Section: Methodsmentioning
confidence: 98%
“…However, a recent national survey indicated that only 16.4% of eligible women, regardless of HIV status, had ever been screened for CC 8. Practical challenges to achieving screening targets include overall low acceptability of CC screening, high loss to follow-up (LTFU) rates, and infrastructure and commodity constraints 9 10…”
Section: Introductionmentioning
confidence: 99%
“…This required both to commit resources for cervical cancer screening. Over the last 6 years VIA screening has expanded to include more than 60,000 women (Orang'o et al, 2016a) (Fig. 1).…”
Section: The Solution: Development Of a Gynecologic Oncology Programmentioning
confidence: 99%